2020
DOI: 10.3390/ma13245841
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pyrolysis Temperature on the Properties of Eucalyptus Wood-Derived Biochar

Abstract: Pyrolysis conditions directly influence biochar properties and, consequently, influence the potential use of biochar. In this study, we evaluated the effects of different pyrolysis temperatures (450, 550, 650, 750, 850, and 950 °C) on the hydrogen potential, electrical conductivity, ash content, yield, volatile matter content, elemental analysis, Fourier-transform infrared spectroscopy results, X-ray diffraction results, scanning electron microscopy results, specific surface area, and micropore volume of eucal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 54 publications
5
30
0
Order By: Relevance
“…A decrease in yield of 7.52% from 400 °C to 600 °C suggests that most of the lignocellulosic material was decomposed, while a decrease of 1.69% from 600 °C to 800 °C, which is much smaller than the previous amount, suggests the formation of more stable biochar with a much lower material loss. This negative effect of temperature on the carbonization yield is consistent with previous studies, such as that reported by Chaves Fernandes et al, where a negative correlation between the pyrolysis temperature and the Eucalyptus biochar yield was found, mainly in the range of 450–650 °C [ 20 ]. Similar behaviors have been shown in other carbonaceous materials, which presented this reduction of yield at higher temperatures until they became lower and constant.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…A decrease in yield of 7.52% from 400 °C to 600 °C suggests that most of the lignocellulosic material was decomposed, while a decrease of 1.69% from 600 °C to 800 °C, which is much smaller than the previous amount, suggests the formation of more stable biochar with a much lower material loss. This negative effect of temperature on the carbonization yield is consistent with previous studies, such as that reported by Chaves Fernandes et al, where a negative correlation between the pyrolysis temperature and the Eucalyptus biochar yield was found, mainly in the range of 450–650 °C [ 20 ]. Similar behaviors have been shown in other carbonaceous materials, which presented this reduction of yield at higher temperatures until they became lower and constant.…”
Section: Resultssupporting
confidence: 92%
“…Table 1 also shows a yield decrease of 7.52% from 400 °C to 600 °C and a moderate decrease of 1.69% from 600 °C to 800 °C. As a lignocellulosic material, sour orange peel can be composed of three main building blocks, namely hemicellulose, cellulose, and lignin, as well as some extractives [ 19 ], it is expected that temperature increase favors the decomposition of these constituents as well as the release of gases and volatiles caused by this decomposition [ 20 ]. A decrease in yield of 7.52% from 400 °C to 600 °C suggests that most of the lignocellulosic material was decomposed, while a decrease of 1.69% from 600 °C to 800 °C, which is much smaller than the previous amount, suggests the formation of more stable biochar with a much lower material loss.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well known that many parameters influence the final characteristics of BC, which is why its production and surface alteration certainly select its final application [16,[26][27][28][29]. When the pollutant is hydrophobic or aromatic, the aromatization of BC is a fundamental characteristic to increase the adsorption capability.…”
Section: Introductionmentioning
confidence: 99%